PENGARUH MOTIVASI INTERNAL DAN EKSTERNAL TERHADAP KINERJA PEGAWAI - Harras, Hadyati (Sekolah Menengah Kejuruan (SMK) Pustek, 2019)
Low public trust in public services became a warning to the regional government, especially the Tigaraksa religious court to organize a good governance system, and one of the efforts is to improve employee performance. The purpose of this study was to analyze the effect of motivation on employee performance. The research method uses quantitative, object of research is Tigaraksa religious court, research sample is employees, sample technique uses simple random, research instrument uses questionnaires, and analysis method uses multiple linear regression. The results showed that internal and external motivation had a significant effect on performance. This finding explains, so that the task is done well then the motivation factor has a big influence, especially the support from the organization in the form of material motivation